THE SALTY TASTE THRESHOLD AND TONGUE CLEANING HABITS IN HEALTHY YOUNG ADULT MALE SMOKERS - Marcella bt Mohamad Azlin; Erna Herawati; Nanan Nur'aeny (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2020)
Introduction: Smoking has adverse effects on the body such as various types of cancer, coronary heart diseases, stroke, peripheral vascular diseases, and oral changes including decreased taste sensation. There have been many studies on the effects of smoking on taste threshold, but specific studies in a group of young adult males and data on the frequency of tongue cleaning habits have not been reported. This study aims to determine the salty taste threshold and tongue cleaning habits in healthy young adult male smokers. Methods: This study was a descriptive cross-sectional study, and the subjects were taken by consecutive sampling. The criteria for the subjects were healthy males, aged 18-24 years old, who had a habit of smoking 10 cigarettes or more per day and had smoked for more than 1 year. A questionnaire was conducted including data on tongue cleaning habits before measuring the salt taste threshold using various concentrations of sodium chloride solution which are 0,012M, 0,014M, and 0,016M. Introduction: Smoking has adverse effects on the body such as various types of cancer, coronary heart diseases, stroke, peripheral vascular diseases, and oral changes including decreased taste sensation. There have been many studies on the effects of smoking on taste threshold, but specific studies in a group of young adult males and data on the frequency of tongue cleaning habits have not been reported. This study aims to determine the salty taste threshold and tongue cleaning habits in healthy young adult male smokers. Methods: This study was a descriptive cross-sectional study, and the subjects were taken by consecutive sampling. The criteria for the subjects were healthy males, aged 18-24 years old, who had a habit of smoking 10 cigarettes or more per day and had smoked for more than 1 year. A questionnaire was conducted including data on tongue cleaning habits before measuring the salt taste threshold using various concentrations of sodium chloride solution which are 0,012M, 0,014M, and 0,016M. Results: Subjects consisted of 76 healthy young adult male smokers for 3-8 years. There were 39%, 53%, and 8% of subjects with a salty taste threshold at concentration 0.012M, 0.014M and 0.016M respectively. Most subjects had a smoking habit for 4 years (36%), and the tongue cleaning habit was not found in the majority of subjects (46%).Conclusion: Most of the subjects had a salty taste threshold higher than normal and more subjects do not have the habit of cleaning the tongue.